2020
DOI: 10.1039/d0ra00049c
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput and untargeted lipidomics approach reveals new mechanistic insight and the effects of salvianolic acid B on the metabolic profiles in coronary heart disease rats using ultra-performance liquid chromatography with mass spectrometry

Abstract: High-throughput lipidomics provides the possibility for the development of new therapeutic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Finally, the chromatographic peaks are integrated and analyzed with standard curves generated by authentic standards. A similar LCMS/MS approach was recently used to study tomato and rice leaves [ 19 , 20 ]. Six sugarcane cultivars were used in this study ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the chromatographic peaks are integrated and analyzed with standard curves generated by authentic standards. A similar LCMS/MS approach was recently used to study tomato and rice leaves [ 19 , 20 ]. Six sugarcane cultivars were used in this study ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been studied as a potential drug for cardiovascular remedy for many years [21,22]. Li et al [23] have revealed the protective influence of SalB in rats with coronary heart disease through high-throughput and non-targeted lipidomics, indicating that SalB has a good influence on coronary heart disease by regulating glycerophospholipid metabolism, sphingolipid metabolism, and arachidonic acid metabolism, inhibiting oxidative stress injury and lipid peroxidation. In the present research, our results exhibit that SalB has a protective influence on CDDP-induced myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have explored the potential therapeutic roles of lipids in human health (48). To access the pharmacological value of sugarcane lipid compounds we have examined their activity against SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%